Multi-scale analysis for promoting integrated watershed management - Rubiano, J.; Quintero, Marcela; Estrada, R.D.; Moreno, Alonso (Informa UK Limited, 2006)
Integrated Watershed Management involves many aspects of the biophysical and socio economic world operating at many different scales. It is a complex process since it involves a wide range of stakeholders that live, and compete for limited resources, at different temporal and spatial scales. In order to gain knowledge about appropriate approaches for integrating natural resources management with rural development strategies, this study details a framework designed to implement research and development activities in the Fúquene watershed of Colombia.